The Role of International Legislation in Protecting the Environment - ALHENDI, Noor (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).16, 2022)
This study deal with the role of international legislation in protecting the environment, and it is a legal issue worthy of international attention. The study revealed that the environment is the ocean that includes living and non-living organisms and what it contains of materials and what surrounds it of air, water and soil and the interactions of any of them and what the human constructs in it. The environment is in the natural, artificial, land, water, and air environment, so it must be protected from pollution with legal texts. And Pollution is the introduction of substances or energy by humans, either directly or indirectly, into the environment, which results in harmful effects that threaten human health, harm living resources or ecosystems, undermine the enjoyment of the environment. The health importance of the environment lies in the impact of the environment on the human being to leave his clear fingerprints on his health. The study proposes the text on provision of criminal penalties to be applied to anyone who harms and pollutes the environment, and the results of the study were that international legislation provided legal protection for the environment, in the law of an international environment, international conventions, and international organizations, and the study relied on the descriptive method to clarify this matter.